Prinsip - prinsip Hukum Perbankan Syariah - Nurfadilla K; Mira Mira; Ilham Ilham (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
The abstract of this journal explains that Islamic banks operate based on Islamic sharia principles that do not recognize the interest system (riba), and instead prioritize the principles of justice, partnership, and profit sharing. Islamic banks were established as an alternative for people who want a financial system that is in accordance with sharia. In this system, financial transactions must be free from elements of usury, gharar (uncertainty), and maisir (gambling), and prioritize honesty and transparency.